Organic farm waste management in degraded banana-coffee-based farming systems in NW Tanzania. (November 2020) - Reetsch, Anika; Feger, Karl-Heinz; Schwärzel, Kai; Dornack, Christina; Kapp, Gerald
Abstract: This study examines how smallholder farmers operate degraded banana-coffee-based farming systems and apply organic farm waste. We surveyed 150 farm households in two districts of the Kagera region in north-west Tanzania (Karagwe and Kyerwa districts). An expert-based typology revealed three groups of farm households that differ in biomass production (high, moderate, low). Households producing high amounts of biomass have integrated a sophisticated farm waste management system, but do not exploit the full potential of organic farm waste as a soil fertiliser and conditioner. The integration of farm waste management decreases in farm households with medium and low biomass production. None of the households is food secure, as they experience seasonality in food production and lack food storage technologies. In farm households with high and medium biomass production, the optimised use of organic farm waste could potentially lead to food security if food storage capacities were also improved. However, farm households with low biomass production will not become food secure with the introduction of organic farm waste management alone, as the land size is too small, and the socio-economic basis for it is lacking. Limited labour remains a major restriction to improving farm waste management. In the future, the safe use of human excreta needs to be fostered in engineering and research, holistic material flow analyses integrating (low-tech) agricultural solutions and concepts investigated, e.g., biochar production, safe use of mineral fertiliser and climate-smart agriculture, and the socio-economic status of female-headed households strengthened, e.g., in farmer field schools and governmental programmes. Graphical abstract: Unlabelled Image Highlights: Smallholder farm households that apply organic farm waste to their fields have higher yields. Female-led households remain the most vulnerable to food security. The potential of organic farm waste in sustaining soil fertility has not been fully realised. Knowledge of organic farm waste management has decreased since the outbreak of HIV/AIDS.